The Relationship Between Carbon Disclosure Project Scores and Global 500 Companies: A Perspective From National Culture - Oktay, Sadiye; Bozkurt, Serdar; Yazici, Kubra (SAGE PUBLICATIONS INC, 2021)
This research aims to examine the relationship between voluntary carbon disclosures and national cultures of Global 500 companies that direct the world economy. The research is essential in terms of showing the results of the Paris agreement, which is considered to have an impact on climate change, one of the most outstanding variables affecting sustainability, in the national context. Our study is one of the few on the sustainability theories (stakeholder, legitimacy, signaling, and system) and the relationship between carbon disclosures and the context of national culture both. As a consequence of this research, the relationships between Carbon Disclosure Project (CDP) data and the national culture to which Global 500 companies belong were determined. In this context, CDP climate scores also differ in five dimensions (uncertainty avoidance, individualism, power distance, long-term orientation, indulgence) other than Hofstede's masculinity dimension. CDP's water security values differ only in the social aspect to avoid uncertainty. Also, we find that the Paris agreement makes a difference in carbon disclosures.
Keywords: carbon disclosure project; national culture; sustainability; Global 500; CORPORATE SOCIAL-RESPONSIBILITY; CLIMATE-CHANGE; SUSTAINABLE DEVELOPMENT; PARIS AGREEMENT; ENVIRONMENTAL PERFORMANCE; VOLUNTARY DISCLOSURE; COUNTRY-LEVEL; VALUES; TRANSPARENCY; EMISSIONS; Social Sciences - Other Topics